AKUNTABILITAS PENGGUNAAN DANA DESA 2020 DI DESA BLEMBEM, KECAMATAN JAMBON, KABUPATEN PONOROGO - Subiyantoro, Subiyantoro (JI@P, 2021)
Accountability in general can be defined as a demand for accountability for fulfilling responsibilities. Accountability really determines the success of policy implementation, especially public policy by the government. The level of budget absorption and management of village funds which continues to experience positive increases from year to year, but in terms of the accountability report, it has not carried out village financial administration properly. On the basis of these problems, this study aims to analyze and describe the accountability of village fund management in Blembem Village, Jambon District, Ponorogo Regency in 2020. The accountability theory in this study uses Ellwood in Mardiasmo (2009: 21) that the management of village funds must be based on honesty and accountability law, accountability process, accountability program and accountability policy.This study uses a descriptive method with a qualitative approach. Research informants using purposive sampling technique. Data collection techniques using in-depth interviews and documentation. The data analysis technique used is interactive analysis consisting of data collection, data condensation, data presentation and conclusion drawing.The results showed that the Blembem Village Government in managing village funds had shown accountability, both from the dimensions of honesty and legal accountability, process accountability, program accountability and policy accountability. From the accountability of honesty and law, it is evident that they are willing to inform community members about the amount of village funds received, do not abuse their positions, do not mark up budgets, and run according to Permendagri No. 113 of 2014 concerning Village Financial Management. The dimension of process accountability shows that the procedures used in managing village funds are quite good in terms of the adequacy of accounting information systems, management information systems, and administrative procedures. In terms of program accountability, it shows that the programs that have been implemented, such as training programs for small industry businesses (sewing training, cake making training, etc.) can benefit the community and can improve the economy and community welfare, even in terms of the capacity of village officials and training at MSMEs still needs optimization and assistance.